Downregulation of PRKCI inhibits osteosarcoma cell growth by inactivating the Akt/mTOR signaling pathway - Qu, Liujing; Xin, Yu; Feng, Jieni; Ren, Xiaolei; Li, Zuming; Chen, Xueru; Miao, Guangyan; Chen, Jiankun; Sun, Chengming; Lu, Yue (Frontiers in Oncology, 2024)
PRKCI is abnormally expressed in various cancers, but its role in osteosarcoma is unknown. This study aimed to explore the biological function of PRKCI in osteosarcoma and its potential molecular mechanism. PRKCI expression was evaluated in osteosarcoma cells lines using Western blot analysis and reverse transcription PCR. CCK-8 assay, colony formation assay, flow cytometry, Transwell assay and wound healing assay were used to detect the proliferation, colony-forming capacity, cell cycle, migration and invasion of osteosarcoma cell when PRKCI was overexpressed or knockdown. The interaction between PRKCI and SQSTM1 was explored using immunoprecipitation. Finally, the protein molecule expression of Akt/mTOR signaling pathway in osteosarcoma was detected when PRKCI was knockdown. Our study found that PRKCI was overexpressed in osteosarcoma cell lines. The overexpression of PRKCI promoted the proliferation and colony-forming capacity of osteosarcoma cells, while silencing PRKCI inhibited the proliferation, colony-forming capacity, migration and invasion of osteosarcoma cells and arrested the cell cycle at G2/M phase. Both PRKCI and SQSTM1 were overexpressed in osteosarcoma. The expression of PRKCI was only related to histological type, while that of SQSTM1 was not related to clinical characteristics. The expression of PRKCI and SQSTM1 in osteosarcoma was higher than that in chondrosarcoma. Knockdown of PRKCI inhibited the proliferation of osteosarcoma cells by inactivating the Akt/mTOR signaling pathway, suggesting that PRKCI was a potential target for osteosarcoma therapy.